Pengaruh Variasi Produk dan Kualitas Produk Terhadap Kepuasan Konsumen Pada Chatime Living World Pekanbaru - Ela Marlianda; Annisa Mardatillah (Pelantar Press, 2025)
This study is to Analyze and Explain the Effect of Product Variation and Product Quality on Consumer Satisfaction at Chatime Living World Pekanbaru. Using Variables (X1) Product Variation: Size, Price, Appearance and Product Availability. Variables (X2) Product Quality: Product Characteristics, Conformity to Specifications, Durability, Reliability and Design. Variables (Y) Consumer Satisfaction: Experience, Customer Expectations and Needs. Type of Descriptive Survey Research with Quantitative Research method. Data Collection Techniques Used: Observation, Questionnaire, Interview and Documentation. Research Results Product Variation contributes 188.45% to Consumer Satisfaction. Product Quality is more dominant with a contribution of 233.31%. This means that although both have a significant influence, product quality has a greater influence in shaping consumer satisfaction. Suggestions for Product Innovation Add new flavor variants to attract consumers. Maintain Quality Ensure that the taste, ingredients, and presentation remain consistent. Improve Service Conduct regular training for Employees. Use customer input for continuous improvement. Focus on the 20-30 year old age segment, especially women, through promotions that are in line with trends